SCIENTIFIC JUSTIFICATION AND PRACTICAL IMPLEMENTATION IN UKRAINE OF THE TELEREHABILITATION SYSTEM FOR BREAST CANCER PATIENTS - Semikopna, T. V.; Syvak, O. V.; Vladymyrova, N. I.; Sayko, O. Y.; Solovyova, V. S.; Kashyrina, O. V.; Vladymyrov, O. A. (Medical Informatics and Engineering, 2025)
Background. Rehabilitation intervention planning for cancer patients should take into account the complex treatment modalities, be focused on improving functioning, preventing secondary complications, and facilitating adaptation or readaptation to community living. The implementation of telerehabilitation technologies makes it possible to provide rehabilitation services during an outpatient phase in a comfortable environment for patients. Materials and methods. The object of the study, using a meta-analysis of data, was breast cancer survivors of different stages of the disease and different age groups who underwent telerehabilitation interventions in numerous global scientific studies. The methodology of the scientific research was based on the International Classification of Functioning, Disability, and Health. For breast cancer, special, comprehensive, and brief core sets of ICFs have been developed. Results. A comprehensive assessment of various aspects of breast cancer survivors’ health using a standardized system and a common language to describe the impact of the disease at different levels is needed to formulate a personalized plan for goal-directed rehabilitation interventions. The determination of measurement tools that can measure functional limitations and monitor outcomes in telerehabilitation is a key aspect in the development of rehabilitation interventions. Rehabilitation activities in telerehabilitation are recommended in numerous clinical guidelines and include physical therapy, psychological counselling, and assistance with social reintegration. The assessment of quality of life has become one of the most important components of cancer care. Conclusions. Scientifically based design of a general model of patient-centred complex cancer telerehabilitation, which includes all the necessary stages, such as rehabilitation examination, and the formation of a personalized rehabilitation plan with monitoring and evaluation of rehabilitation outcome measures.